Bioenergy technology development in Nigeria - pathway to sustainable energy development. (29th April 2019) - Oyedepo, Sunday O.; Dunmade, Israel S.; Adekeye, Tunde; Attabo, Ahme A.; Olawole, Olukunle C.; Babalola, Philip O.; Oyebanji, Joseph A.; Udo, Mfon O.; Kilanko, Oluwaseun; Leramo, Richard O.
In Nigeria, high and outrageous energy cost constitutes a serious challenge to all aspects of the economy. And this has been a subject of concern in the country over a period of time. A dependable and renewable energy source is of utmost desire to strengthen the nation's economy and this urgent need cannot be overlooked. As a result of the erratic and expensive power supply to the national grid, it has become ultimately necessary to search for other inexpensive sources of energy to meet the ever increasing energy needs for rural and urban dwellers. In view of the above energy situation in Nigeria, this paper aimed at carrying out a comprehensive review on bioenergy technology option as a pathway to achieving sustainable energy development in the country. The potential, current progressive stages, and prospects of bioenergy conversion techniques, in the Nigeria context, are discussed. The barriers to bioenergy technology development in Nigeria with possible solutions are also presented.